Genetic analysis of the endangered Cleveland Bay horse: A century of breeding characterised by pedigree and microsatellite data - Dell, Andrew (PLoS One, 2020)
The Cleveland Bay horse is one of the oldest equines in the United Kingdom, with pedigree data going back almost 300 years. The studbook is essentially closed and because of this, there are concerns about loss of genetic variation across generations. The breed is one of five equine breeds listed as “critical” (<300 registered adult breeding females) by the UK Rare Breeds Survival Trust in their annual Watchlist. Due to their critically endangered status, the current breadth of their genetic diversity is of concern, and assessment of this can lead to improved breed management strategies. Herein, both genealogical and molecular methods are combined in order to assess founder representation, lineage, and allelic diversity. Data from 15 microsatellite loci from a reference population of 402 individuals determined a loss of 91% and 48% of stallion and dam lines, respectively. Only 3 ancestors determine 50% of the genome in the living population, with 70% of maternal lineage being derived from 3 founder females, and all paternal lineages traced back to a single founder stallion. Methods and theory are described in detail in order to demonstrate the scope of this analysis for wider conservation strategies. We quantitatively demonstrate the critical nature of the genetic resources within the breed and offer a perspective on implementing this data in considered breed management strategies.